2002
DOI: 10.1128/mcb.22.15.5467-5478.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Colonic Repressor Element Regulates Intestinal Gene Expression by Interacting with Cux/CDP

Abstract: Intestinal gene regulation involves mechanisms that direct temporal expression along the vertical and horizontal axes of the alimentary tract. Sucrase-isomaltase (SI), the product of an enterocyte-specific gene, exhibits a complex pattern of expression. Generation of transgenic mice with a mutated SI transgene showed involvement of an overlapping CDP (CCAAT displacement protein)-GATA element in colonic repression of SI throughout postnatal intestinal development. We define this element as CRESIP (colon-repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
1
24
0
1
Order By: Relevance
“…Indeed, besides the previously reported inhibitory mechanisms of intestinal cell differentiation (Houde et al, 2001;Rings et al, 2001;Boudreau et al, 2002a;Tou et al, 2004;Mariadason, 2008;Verzi et al, 2010) detailed above, our studies using the two distinct intestinal cells models Caco-2/15 and HIEC CDX2/HNF-1a showed that the activity of the PRC2 component of PcG specifically repressed the expression of a number of terminal differentiation markers. In situ, the cornerstone PRC2 component SUZ12 was identified in a significant proportion of colon tumours and found predominantly in the TA zone in the normal small intestine suggesting that PcG proteins may also participate in the repressive mechanism of terminal differentiation in vivo.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, besides the previously reported inhibitory mechanisms of intestinal cell differentiation (Houde et al, 2001;Rings et al, 2001;Boudreau et al, 2002a;Tou et al, 2004;Mariadason, 2008;Verzi et al, 2010) detailed above, our studies using the two distinct intestinal cells models Caco-2/15 and HIEC CDX2/HNF-1a showed that the activity of the PRC2 component of PcG specifically repressed the expression of a number of terminal differentiation markers. In situ, the cornerstone PRC2 component SUZ12 was identified in a significant proportion of colon tumours and found predominantly in the TA zone in the normal small intestine suggesting that PcG proteins may also participate in the repressive mechanism of terminal differentiation in vivo.…”
Section: Discussionmentioning
confidence: 87%
“…Because the main pro-differentiation transcription factors are expressed in these cells, one may consider various mechanisms known to negatively modulate their transcriptional activity such as post-translational modifications (Houde et al, 2001;Rings et al, 2001), expression of transcriptional repressors (Boudreau et al, 2002a) and/or epigenetic mechanisms such as histone modifications (Tou et al, 2004;Mariadason, 2008;Verzi et al, 2010). Another possibility not yet investigated could be epigenetic control of gene expression via polycomb group (PcG) proteins.…”
Section: Introductionmentioning
confidence: 99%
“…‫,ء‬ p Ͻ 0.05; ‫,ءء‬ p Ͻ 0.01. small intestine vs colon are poorly understood. For the small intestinal specific gene sucrase isomaltase, tissue selectivity is achieved through the combination of HNF-1␣, GATA-4, and Cdx-2 (48), together with active suppression of this gene in the colon (57). Promoter analysis using MatInspector predicted a binding site for this repressor (CLOX/CDP) within the CCL25 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…De nombreuses pathologies de l'épithélium intestinal, en l'occurrence le cancer colorectal, découlent directement du dérègle-ment des mécanismes régissant cet équilibre. L'utilisation de modèles cellulaires et de souris transgéniques a montré l'importance positionnelle et combinatoire de certains facteurs de transcription dans la régulation de marqueurs associés à la différencia-tion épithéliale tout le long du tube digestif [1,2]. CDX2, un facteur de transcription exprimé spécifiquement dans l'épithélium intestinal, repré-sente un candidat important dans la mise en oeuvre d'un programme spécifique de différenciation temporelle en fonction des segments de l'épithélium du tube digestif.…”
unclassified